Does environmental regulation decline or boost housing prices? Empirical evidence from panel data of Chinese cities - Peng, Weibin; Wu, Manman; Xu, Jiaxin (Frontiers in Sustainable Cities, 2025)
China's industrialization process, transitioning from a heavy industry-oriented strategy to ecological civilization construction in the new era, has shaped the intrinsic connection between environmental regulation and the real estate market. Based on panel data from the government work reports and economic development of 280 prefecture-level cities in China from 2003 to 2023, this study constructs an environmental regulation index using an improved TF-IDF algorithm to examine the impact of environmental regulation on housing prices and its underlying mechanisms. It innovatively employs historical railway inauguration data in China as an instrumental variable. Fixed-effects model results reveal that the impact of environmental regulation on housing prices exhibits a U-shaped pattern, with a predominantly inhibitory effect at the current stage. The mediating effect model further reveals that environmental regulation indirectly affects housing prices through promoting industrial structure upgrading and green technological innovation. The industrial green transformation transmission mechanism in the impact of China's environmental regulation on housing prices may become one of the micro-implementation pathways for the global sustainable development goals.